2020
DOI: 10.1039/d0nj04288a
|View full text |Cite
|
Sign up to set email alerts
|

A down converting serine-functionalised NaYF4:Ce3+/Gd3+/Eu3+@NaGdF4:Tb3+ photoluminescent probe for chemical sensing of explosive nitroaromatic compounds

Abstract: In this contribution, we explored a novel serine-functionalised NaYF4:Ce3+/Gd3+/Eu3+@NaGdF4:Tb3+ core–shell nanophosphor as a down-converting photoluminescent probe for efficient sensing of nitroaromatic explosives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Tashi et al reported a facile hydrothermal synthesis and characterization of hexagonal Eu 3+ doped and Eu 3+ /Ce 3+ co-doped NaGdF 4 nanophosphors and the influence of different radii of rare-earth ions on crystal morphology. Furthermore, on the basis of this study, they also demonstrated a Ser-CS (serine-functionalized NaYF 4 :Ce 3+ /Gd 3+ /Eu 3+ @NaGdF 4 :Tb 3+ core shell) nanophosphor for the effective detection of nitroaromatic derivatives …”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Tashi et al reported a facile hydrothermal synthesis and characterization of hexagonal Eu 3+ doped and Eu 3+ /Ce 3+ co-doped NaGdF 4 nanophosphors and the influence of different radii of rare-earth ions on crystal morphology. Furthermore, on the basis of this study, they also demonstrated a Ser-CS (serine-functionalized NaYF 4 :Ce 3+ /Gd 3+ /Eu 3+ @NaGdF 4 :Tb 3+ core shell) nanophosphor for the effective detection of nitroaromatic derivatives …”
Section: Resultsmentioning
confidence: 80%
“…Furthermore, on the basis of this study, they also demonstrated a Ser-CS (serine-functionalized NaYF 4 :Ce 3+ / Gd 3+ /Eu 3+ @NaGdF 4 :Tb 3+ core shell) nanophosphor for the effective detection of nitroaromatic derivatives. 32 Also, the heating rate and the maximum reaction temperature needed to be controlled. When the heating rate reached above 8 K/s, CeOF would appear in the product, which was difficult to remove.…”
Section: → + +mentioning
confidence: 99%
“…Nitroaromatic compounds are an important class of chemicals widely used in chemical industries. 1,2 They are the basic backbone of some pesticides and highly substituted derivatives are powerful explosives for military and civilian use. 2 They are also very useful reaction intermediates in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is used for the synthesis of polymers, dyes, pharmaceuticals, pesticides and cosmetics among others. 1,2,4 As a consequence, large amounts of nitroaromatic compounds from the chemical industry are discharged intentionally or unintentionally into the environment, with serious damages. 4,5 Being rarely produced naturally, their biodegradation is difficult.…”
Section: Introductionmentioning
confidence: 99%
“… 39 Tashi et al fabricated down converting serine functionalized NaGdF 4 :Eu 3+ /Ce 3+ @NaGdF 4 :Tb 3+ core–shell nanomaterial for the selective and sensitive detection of picric acid. 40 Abbas and co-workers developed C-encapsulated three-dimensional Cu nano-pyramids (C@3DCu-PY) sensors for the control and monitoring of phenolic compounds. 41 Saleemi et al reported a novel OVs rich spinel ZnFe 2 O 4 micro-spheres (ZF-Ms) sensor for the effective detection of As 3+ metal ion present in underground water.…”
Section: Introductionmentioning
confidence: 99%